2009
DOI: 10.1371/journal.pone.0004118
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Respiratory Alphaherpesvirus Infection Using RNA Interference

Abstract: BackgroundEquine herpesvirus type 1 (EHV-1), a member of the Alphaherpesvirinae, is spread via nasal secretions and causes respiratory disease, neurological disorders and abortions. The virus is a significant equine pathogen, but current EHV-1 vaccines are only partially protective and effective metaphylactic and therapeutic agents are not available. Small interfering RNAs (siRNA's), delivered intranasally, could prove a valuable alternative for infection control. siRNA's against two essential EHV-1 genes, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…These complexes were characterized by a size of almost 400 nm and a zeta potential of À8 mV. siRNA delivery has been attempted in vivo to the lung in the absence of carrying molecules and nevertheless obtaining positive results (Fulton et al, 2009;Gutbier et al, 2010;Rosas-Taraco et al, 2009;Senoo et al, 2010), with some reports showing no significant difference in gene silencing efficiency between naked siRNA and the use of delivery vectors (Bitko et al, 2005;Fulton et al, 2009). It has been hypothesized that the siRNA modifications transfection or the damage of the airway epithelium caused by viral infection, or by other pathological processes, may have caused increased internalization of naked siRNAs (Fujita et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…These complexes were characterized by a size of almost 400 nm and a zeta potential of À8 mV. siRNA delivery has been attempted in vivo to the lung in the absence of carrying molecules and nevertheless obtaining positive results (Fulton et al, 2009;Gutbier et al, 2010;Rosas-Taraco et al, 2009;Senoo et al, 2010), with some reports showing no significant difference in gene silencing efficiency between naked siRNA and the use of delivery vectors (Bitko et al, 2005;Fulton et al, 2009). It has been hypothesized that the siRNA modifications transfection or the damage of the airway epithelium caused by viral infection, or by other pathological processes, may have caused increased internalization of naked siRNAs (Fujita et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies utilizing siRNA were designed to avoid systemic administration. The routes of administration in these studies were subcutaneous [120], intradermal [121], intraocular [122], intralesional [123], intranasal [124][125][126], intratracheal [127,128], intrathecal [129][130][131], intracerebral [132,133], intratumoral [134][135][136][137], intravaginal [138,139], intrarectal [140], transdermal [141] and topical [142].…”
Section: Triplex-forming Oligodeoxynucleotidesmentioning
confidence: 99%
“…For equine viruses, in vitro studies have shown that siRNA can reduce viral titers in cell cultures infected with equine arteritis virus (Heinrich et al, 2009), African horse sickness virus (Stassen et al, 2007) or Venezuelan equine encephalitis virus (O'Brien, 2007). More specifically for EHV-1, RNA interference has been effective both in vitro and in vivo, as assessed by a reduction in plaque formation in cell cultures and a reduction in clinical signs (weight loss) and viral replication within lung tissue in a murine model of EHV-1 infection (Fulton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%